The Influence of Sponsored Post Towards The Urge to Buy Implusively on The Information Technology System of The Social Media of Instagram - Rahayu, Anggrainni; Baridwan, Zaki (AKRUAL: JURNAL AKUNTANSI, 2020)
This study examines the influence between variables of similarity, vicarious expression, aesthetic appeal, cognitive trust, affective trust, product affection, and urge to buy impulsively on the social media of Instagram. The method used for collecting the data in this study was the survey method. The samples were collected using the convenient sampling techniques. The utilized data analysis techniques used in this study were validity testing, reliability testing, and hypothesis testing. The data analysis process was conducted with the aid of Partial Least Square (PLS). The results of this study showed that similarity positively influences cognitive and affective trust, vicarious expression and aesthetic appeal positively influence product affection, cognitive trust positively influences affective trust, affective trust positively influences product affection, cognitive trust does not influence the urge to buy impulsively, and affective trust and product affection positively influence the urge to buy impulsively.